Onychomadesis Secondary Erythroderma Exfoliative due to Ciprofloxacin - Patricia Chang; Monica Vanesa Vásquez Acajabón (Our Dermatology Online, 2014)
Female patient 63 years old who was hospitalized due to erythroderma exfoliative (Fig. 1) after taking ciprofloxacin by urinary tract infection, 4 weeks later we began to observe the detachment of the finger and toenails from the proximal nail fold predominantly on the thumbs (Fig. 2), and the diagnosis of onychomadesis was done. Nail diseases are common but no all people and doctors know about nail changes due to drug reaction or systemic diseases.